2017
DOI: 10.1002/ppul.23655
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected results in infant multiple breath washout: Is the truth hidden in the washin?

Abstract: Unexpected Results in Infant Multiple Breath Washout: Is the Truth Hidden in the Washin?Recently, a refined software algorithm for infant multiple breath washout (MBW) analysis was proposed aiming to improve the accuracy of tracer gas evaluation. 1 The use of this algorithm revealed high lung clearance index (LCI) values in infants with cystic fibrosis (CF) which were previously found to be normal. Foong et al. used this algorithm to retrospectively analyze infant MBW data from healthy, CF, and preterm infants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The inability to retrieve absolute SF 6 concentrations remains one of the major drawbacks of the old setup. As the MM‐step determines the relevant SF 6 concentration per breath, any manipulation in the washout curve (eg, cutting the end of the washout) will affect MBW indices.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The inability to retrieve absolute SF 6 concentrations remains one of the major drawbacks of the old setup. As the MM‐step determines the relevant SF 6 concentration per breath, any manipulation in the washout curve (eg, cutting the end of the washout) will affect MBW indices.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to analysis, flow, volume, MM, and environmental corrections were applied as previously described . End‐tidal SF 6 concentration (Cet,SF 6 ) per breath was estimated indirectly from the MMms signal between 65 and 95% of expired volume based on fixed MM differences between washin and washout [end‐inspiratory (EIMM)‐step] . Due to the lack of signals for other gas components (O 2 , CO 2 , N 2 ) the software provided only normalized end‐tidal SF 6 values per breath for the whole washout curve.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of the multiple breath washout test (MBW) technique to measure the lung clearance index (LCI) has been increasingly used to assess ventilation inhomogeneity, but measurement of LCI in infants is challenging. Kentgens et al demonstrated the importance of determining an appropriate washin time of a foreign tracer gas (eg, SF6) using a commercially available MBW device . The current system requires the operator to manually stop the washin before beginning the washout.…”
Section: Introductionmentioning
confidence: 99%